1985
DOI: 10.1017/s002202990002389x
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis and the distribution of lipase activity in bovine milk in relation to stage of lactation and time of milking

Abstract: The increase in levels of free fatty acids (FFA) in morning and afternoon milk after 48 h cold storage at 5 °C was determined at two stages of lactation in milk from 96 cows. Lipolysis was positively correlated to day of lactation (r = 0-6, P < 0-001), while the correlations between lipolysis and milk yield and fat content respectively were due to these factors being related to day of lactation. In afternoon milk the level of FFA increased almost three times above that in morning milk. Lipolysis was closely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
2
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 14 publications
5
18
2
2
Order By: Relevance
“…Auldist et al (1996) reported that Cheddar cheese made using LL milk had a lower flavour score with 'lipolytic' or 'oxidized' flavour notes, and attributed this to a high concentration of FFAs in LL milk or from increased lipolytic activity by lipoprotein lipase (LPL). The activity of LPL associated with the cream fraction was reported to increase with SOL (Ahrne´& Bjo¨rck, 1985), but its contribution to lipolysis in Cheddar cheese is unclear (Fox & Stepaniak, 1993). LPL is extensively inactivated by high-temperature short-time (HTST) treatment (72 C Â 15 s) (Deeth & Fitz-Gerald, 1983), but Driessen (1989) reported that heat treatment of 78 C Â 10 s is required for its complete inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Auldist et al (1996) reported that Cheddar cheese made using LL milk had a lower flavour score with 'lipolytic' or 'oxidized' flavour notes, and attributed this to a high concentration of FFAs in LL milk or from increased lipolytic activity by lipoprotein lipase (LPL). The activity of LPL associated with the cream fraction was reported to increase with SOL (Ahrne´& Bjo¨rck, 1985), but its contribution to lipolysis in Cheddar cheese is unclear (Fox & Stepaniak, 1993). LPL is extensively inactivated by high-temperature short-time (HTST) treatment (72 C Â 15 s) (Deeth & Fitz-Gerald, 1983), but Driessen (1989) reported that heat treatment of 78 C Â 10 s is required for its complete inactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Suhren et al . (), Ahrne and Bjorck () reported that free fatty acid levels were higher when shorter milking intervals were used. O'Brien et al .…”
Section: Husbandry Factors Affecting the Composition Of Bovine Milkmentioning
confidence: 99%
“…Higher activity is associated with its presence in fat fraction of milk. Activity of lipase in milk fat increases with the advancement in lactation stages [21]. The lipolysis process is of major apprehension in the dairy industry, as rancid off flavors are produced in milk and milk products during this phenomenon [22].…”
Section: Lipases and Esterasesmentioning
confidence: 99%